Levinas, Derrida i eschatoteleologia człowieka - Kałużny, Damian (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
This paper presents critics of teleological unity of western philosophy developed by Emmanuel Levinas and Jacques Derrida. One of the key elements of maintained critics is an attempt to redefine western concept of human being which is based on transcendental analyses. The article has two aims. The first isto show that presented by Derrida and Levinas concept of the Other which transcend teleological paradigm has to be formulated insid this paradigm. Philosophies of the Other are then not negative but rather affirmative critics of western philosophy. The second aim is to show that project of overcome the  ontological poleof hu an’s temporal unity can be interpreted as the critic of critic.